1974
DOI: 10.1088/0022-3727/7/9/313
|View full text |Cite
|
Sign up to set email alerts
|

The DC and RF resistivity of discontinuous metal films: a size effect theory

Abstract: A model based on the Mayadas-Shatzkes theory of polycrystalline films is proposed to represent discontinuous films in which island boundaries are considered to be partially reflecting planes, the coefficient of reflection at the boundaries being equivalent to the energy associated with charge transfer from one island to the neighbouring one. The relation between DC resistivity and the thickness of discontinuous films is discussed, and a quantitative picture is presented. The resistivity at radio frequencies, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

1979
1979
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…It has been known since the 1930s that very thin, evaporated metallic films exhibit a decrease in resistance as the frequency of the applied potential increases (3,4). This behavior is physically attributed to the presence of interisland capacitance, whose impedance decreases with increasing frequency (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). In an effort to interpret this phenomenon, the interisland capacitance has been modeled as a continuous distribution (5, 6), as a discrete parameter (7), and as a mixture of the two (8).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…It has been known since the 1930s that very thin, evaporated metallic films exhibit a decrease in resistance as the frequency of the applied potential increases (3,4). This behavior is physically attributed to the presence of interisland capacitance, whose impedance decreases with increasing frequency (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). In an effort to interpret this phenomenon, the interisland capacitance has been modeled as a continuous distribution (5, 6), as a discrete parameter (7), and as a mixture of the two (8).…”
mentioning
confidence: 99%
“…In an effort to interpret this phenomenon, the interisland capacitance has been modeled as a continuous distribution (5, 6), as a discrete parameter (7), and as a mixture of the two (8). However, unless a film is ultrathin (<30 A), it has been shown that the effect of distributed capacitance on the frequency-dependent resistance is negligible (9). This behavior is manifested because the interisland capacitance, corresponding to the separation between large islands, predominates.…”
mentioning
confidence: 99%
See 3 more Smart Citations